Ação, pretensão e processo penal : por uma teoria da acusação - Boschi, Marcus Vinicius (2013)
This thesis has, as an objective, to discuss the access to courts right of action from the penal procedure perspective and to pursuit the claim as the propelling element of jurisdiction. From this first premise, it is necessary to point out the need to abandon the General Theory of Procedural Law and the need to reconstruct the complex prosecuting and defending actions from a different perspective, analyzing the theories of action and their requirements, the procedure, the object of the procedure, and proposing the modifications of the judicial institutes from this analysis. With this proposal, we find, amongst other things, that the right of action is manifested in the offering of charges or the dismissal of them, since what it authorizes it is the formulation of the punitive claim.